Natural gas hydrate resources and hydrate technologies: a review and analysis of the associated energy and global warming challenges - Yu, Yi-Song; Zhang, Xianwei; Liu, Jian-Wu; Lee, Yohan; Li, Xiao-Sen (Energy & environmental science, 2021)
The new scenario involving the rapid energy supply transition from oil-based to natural gas-based undoubtedly affects the future carbon capture and storage (CCS) and offers an opportunity for the use of natural gas hydrates (NGHs). NGHs account for one-third of the mobile organic carbon on Earth, acting as a carbon storage reservoir in the carbon cycle. Hydrate-based technologies including CO 2 capture, CO 2 separation, and natural gas storage and transportation can also be used to reduce greenhouse gas (CO 2 , CH 4 ) emissions and have excellent application potential. However, the implications of the energy supply transition, NGH extraction, and hydrate-based technologies for future climate change mitigation have not been deeply recognized. This paper comprehensively discusses the global energy supply and environmental challenges and transitions, and NGHs and their role in the energy supply, carbon cycle, and historical and future climate change, and summarizes the state-of-the-art developments in hydrate-based technologies and NGH exploitation methods and their potential environmental impacts, thereby providing a perspective on the roles of NGHs and their related technologies in the future energy supply and climate change mitigation. In all of these areas, we focus on identifying future CCS challenges and the technological development risk imposed by a natural gas-based global economy and NGH utilization, which should be highlighted in the next several decades. The roles of natural gas hydrates and their related technologies in the future energy supply, carbon cycle and climate change mitigation.